2016
DOI: 10.1055/s-0036-1596053
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Neurally Adjusted Ventilatory Assist in Premature Infants Postextubation

Abstract: Neurally adjusted ventilatory assist (NAVA) has distinct advantages when used invasively compared with conventional ventilation techniques. Evidence supporting the use of noninvasive NAVA is less robust, especially in the very low birth weight (VLBW) population. To determine whether synchronized noninvasive ventilation via neurally adjusted ventilatory assist (NIV NAVA) supports ventilation postextubation in premature infants. A retrospective analysis of a cohort of twenty-four former VLBW (<1.5 kg) infants fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In addition, one cross‐over study comparing NIV‐NAVA and NIPPV in preterm infants reported a reduction in peak inspiratory pressure (PIP), inspiratory O 2 fraction (FiO 2 ) and the frequency of desaturation with NIV‐NAVA . Another study using NIV‐NAVA for very low‐birthweight infants noted a reduction in partial pressure of CO 2 in a capillary blood gas (pCO 2 ) . NIV‐NAVA is considered to have increased respiratory support ability compared with conventional modalities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, one cross‐over study comparing NIV‐NAVA and NIPPV in preterm infants reported a reduction in peak inspiratory pressure (PIP), inspiratory O 2 fraction (FiO 2 ) and the frequency of desaturation with NIV‐NAVA . Another study using NIV‐NAVA for very low‐birthweight infants noted a reduction in partial pressure of CO 2 in a capillary blood gas (pCO 2 ) . NIV‐NAVA is considered to have increased respiratory support ability compared with conventional modalities.…”
mentioning
confidence: 99%
“…8 Another study using NIV-NAVA for very low-birthweight infants noted a reduction in partial pressure of CO 2 in a capillary blood gas (pCO 2 ). 9 NIV-NAVA is considered to have increased respiratory support ability compared with conventional modalities. Therefore, NIV-NAVA may be superior to other NIV for respiratory support after extubation in preterm infants.…”
mentioning
confidence: 99%
“…Conventional NIV prevents obstructive apnea by generating higher airway pressure, which can easily lead to lung injury and inadequate respiratory support. Conversely, NIV-NAVA continuously adjusts ventilation pressure and volume based on neural feedback from the respiratory center in preterm infants, and even reduces pCO 2 after extubation 20,43 . If apnea occurs NIV-NAVA can provide backup ventilation, shortening the apnea period and relieving hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Yagui et al conducted a RCT (n = 123) comparing NIV-NAVA vs. NCPAP as the primary support in infants with BW <1500 g. There was no difference noted in the primary outcome of need for intubation prior to 72 hours of life, or for the secondary outcome of BPD, between the two groups [82]. Other small RCTs have shown that NIV-NAVA is as effective as NCPAP in preventing extubation failure, but large RCTs studying the outcome of BPD in extremely preterm infants are needed before NIV-NAVA can be routinely recommended [83][84][85][86][87].…”
Section: Non-invasive Neurally Adjusted Ventilatory Assistmentioning
confidence: 91%